207k views
23 votes
What is the first step in solving the system shown below using substitution? 2x=y-1 y=3x

User Lhuber
by
5.1k points

2 Answers

7 votes

Explanation:

At first put the value of y that is 3x in equation 2x=y-1.

Then put the value of x in equation y=3x that comes from the first solving part.

User Sasidhar Vanga
by
5.2k points
5 votes

Answer:

you have to solve the first equation for y

Explanation:

User Reos
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.